In silico analysis of BRCA1 and BRCA2 missense variants and the relevance in molecular genetic testing - Kok-Siong Poon (Nature Portfolio, 2021)
Abstract Over the years since the genetic testing of BRCA1 and BRCA2 has been conducted for research and later introduced into clinical practice, a high number of missense variants have been reported in the literature and deposited in public databases. Polymorphism Phenotyping v2 (PolyPhen-2) and Sorting Intolerant from Tolerant (SIFT) are two widely applied bioinformatics tools used to assess the functional impacts of missense variants. A total of 2605 BRCA1 and 4763 BRCA2 variants from the ClinVar database were analysed with PolyPhen2 and SIFT. When SIFT was evaluated alongside PolyPhen-2 HumDiv and HumVar, it had shown top performance in terms of negative predictive value (NPV) (100%) and sensitivity (100%) for ClinVar classified benign and pathogenic BRCA1 variants. Both SIFT and PolyPhen-2 HumDiv achieved 100% NPV and 100% sensitivity in prediction of pathogenicity of the BRCA2 variants. Agreement was achieved in prediction outcomes from the three tested approaches in 55.04% and 68.97% of the variants of unknown significance (VUS) for BRCA1 and BRCA2, respectively. The performances of PolyPhen-2 and SIFT in predicting functional impacts varied across the two genes. Due to lack of high concordance in prediction outcomes among the two tested algorithms, their usefulness in classifying the pathogenicity of VUS identified through molecular testing of BRCA1 and BRCA2 is hence limited in the clinical setting.